The impact of IFRS 16 on a renewable energy Portuguese company - Santos, Flávia Carvalho dos (2021)
Before 2016, lease accounting was regulated by IAS 17, which did not require operational leases to be included in the balance sheet. With the issue of IFRS 16, all leases are expected to be accounted on the balance sheet. This project assesses the potential impact derived from this change, focusing on an ex ante approach of a case study from a Portuguese company present in the Renewable Energy sector. The results show an impact on the financial position of the company which corroborate previous researches and further emphasize the need for companies to prepare as to minimize IFRS 16 impact.